Persentase Peranan Komitmen Organisasi, Kepuasan Kerja, dan Budaya Organisasi Dalam Meningkatkan Layanan Pegawai di Dinas TPH Provinsi Sumatera Utara - Julaina Nawar; Rukmini Rukmini; Wan Dian Safina; Toni Hidayat (CERED Indonesia Institute, 2022)
This research activity uses a quantitative research method approach with expost facto type which aims to test each role percentage, either partially or simultaneously. The population of this research is 160 employees with a precision of 5% so that the sample is 114 employees. Based on the results of testing the first hypothesis (H1) partially, the variable of organizational commitment plays a significant and significant role on the quality of employee services by 0.021, the results of testing the second hypothesis (H2) partially, the variable job satisfaction plays a significant and significant role on the quality of employee services by 0.023, the results of hypothesis testing the third (H3) partially, the organizational culture variable plays a significant and significant role on the quality of employee service. equal to 0.000, the results of testing the fourth hypothesis (H4) simultaneously with the F test, the variables of organizational commitment, job satisfaction and organizational culture simultaneously play a significant and significant role on the quality of employee services, which together affect the quality of employee services by 25.5% with the multiple regression equation is Y =17.001+0.156 X1+0.090X2+0.172X3+?.